Yield compensation in castor (Ricinus communis L.) with nipping of different order spikes: Yield compensation in castor (Ricinus communis L.) with nipping of different order spikes - P LAKSHMAMMA,; LAKSHMI PRAYAGA, (Journal of Oilseeds Research, 2020)
An experiment was conducted at IIOR to study sink strength and partitioning of assimilates to sink with nipping of different order spikes at initiation or at full expansion stage. Nipping of one spike order at any stage did not show significant reduction in castor seed yield and compensated from next order spikes.